Epidemiology of community-acquired pneumonia and implications for vaccination of children living in developing and newly industrialized countries: A systematic literature review. Issue 9 (1st September 2016) - DeAntonio, Rodrigo; Yarzabal, Juan-Pablo; Cruz, James Philip; Schmidt, Johannes E.; Kleijnen, Jos
ABSTRACT: This systematic review evaluated the epidemiology of community-acquired pneumonia in children <6 y of age within 90 developing and newly industrialized countries. Literature searches (1990–2011), based on MEDLINE, EMBASE, Cochrane, CAB Global Health, WHO, UNICEF, country-specific websites, conferences, health-technology-assessment agencies, and the reference lists of included studies, yielded 8, 734 records; 62 of 340 studies were included in this review. The highest incidence rate among included studies was 0.51 episodes/child-year, for children <5 y of age in Bangladesh. The highest prevalence was in Chinese children <6 months of age (37.88%). The main bacterial pathogens were Streptococcus pneumoniae, Haemophilus influenzae and Mycoplasma pneumoniae and the main viral pathogens were respiratory syncytial virus, adenovirus and rhinovirus. Community-acquired pneumonia remains associated with high rates of morbidity and mortality. Improved and efficient surveillance and documentation of the epidemiology and burden of community-acquired pneumonia across various geographical regions is warranted.